Using the Sakai Learning Management System to change the way Distance Education nursing students learn: are we getting it right?. (1st September 2020) - Tagoe, Michael A.; Cole, Yaa
ABSTRACT: The popularity of LMSs tools and the different levels of interaction they offer have influenced learning. Interest in the use of technology among nursing students has risen and the need to find out how nursing students use Learning Management Systems to learn has become more critical now in developing countries and universities. Whilst LMSs initial focus had been on the administration of learning, there is the recent interest in how these LMS tools effectually result in learning and student satisfaction. The aim of the study was to explore whether students using LMSs such as Sakai to learn differently as they interact with their course content, their instructors and peers. Collaborative and communicative tools such as Wikis, Blogs and charts were not used intensively. The study found that students were not interacting effectively with their tutors. The lack of social presence has led to the use WhatsApp and Telegram by student groups as opportunities to enhance social presence. The findings suggest that effective use of Sakai CLE collaborative and communication tools can enhance interaction between students and content, instructors and students and among students and their overall learning.